Anthropometric parameters, but not aerobic fitness, associates with vascular reactivity of blood pressure in men - Reginaldo Luiz Nascimento; Francisco Navarro; Mario Sevilio Junior; Ricardo Ariel Costa Souza; Sérgio Rodrigues Moreira (Desafio Singular, 2014)
The aim of this study was to verify the association between anthropometric parameters and aerobic fitness with vascular reactivity of blood pressure (VRBP) at healthy male subjects. It was assessed in forty apparently healthy male (27.3 ± 6.3 years; 77.2 ± 11.5 kg; 175.7 ± 6.9 cm) the body mass index (BMI), waist circumference (WC), waist-rip ratio (WRR), body fat (%BF), maximum oxygen uptake (VO2max) and a VR test of BP (Cold Pressor Test - CPT) with immersion of hand in the water (4º Celsius during 1 min). There was no association between aerobic fitness (VO2max below or above of mean and relationship test) and VRBP (p> 0.05). Anthropometric indicators as BMI (r= 0.31 / 0.54), WC (r= 0.30 / 0.49), WRR (r= 0.30 / 0.36) and %BF (r= 0.31 / 0.35) showed positive relationships with VRBP (p< 0.05). However, only WC during the CPT (β= 0.30 / 0.43) and BMI after the CPT (β= 0.54 / 0.81) were predictors of VRBP (p≤ 0.05). We conclude that anthropometric indicators showed independents relationships with VRBP. Nevertheless, only the WC (during) and BMI (after) were significant predictors of VRBP, suggesting that body adiposity, independent of aerobic fitness, have an important role as a cardiovascular risk factor.